2017
DOI: 10.14704/nq.2017.15.4.1121
|View full text |Cite
|
Sign up to set email alerts
|

The Depression/Schizophrenia Continuum: Does Cytoskeletal Tensegrity Play a Role?

Abstract: There is mounting evidence that schizophrenia and depression are polar extremes of the same processes. The neuronal microtubule cytoskeleton is regulated through the actions of microtubule-associated proteins, the centrosome, tubulin posttranslational modifications and differential expression of tubulin isoforms. It is beginning to be thought that they may be important in the development of consciousness itself. It is proposed here that cytoskeletal tensegrity architecture plays a pivotal role in the etiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…NMDA receptor signalling influences the reorganisation of cytoskeleton (Forsyth and Lewis, 2017). Microtubule dysfunction has been previously reported in SZ and other psychiatric disorders (Gardiner, 2017;Marchisella et al, 2016). An over representation of de novo mutation encompassing genes from activity-regulated cytoskeleton-associated protein complex in SZ has been previously reported .…”
Section: Discussionmentioning
confidence: 97%
“…NMDA receptor signalling influences the reorganisation of cytoskeleton (Forsyth and Lewis, 2017). Microtubule dysfunction has been previously reported in SZ and other psychiatric disorders (Gardiner, 2017;Marchisella et al, 2016). An over representation of de novo mutation encompassing genes from activity-regulated cytoskeleton-associated protein complex in SZ has been previously reported .…”
Section: Discussionmentioning
confidence: 97%
“…In a previous paper [42], I suggested that depression, bipolar syndrome, and schizophrenia (and other conditions besides) may be malfunctions of the nervous system cytoskeletal tensegrity framework, particularly in the brain. Indeed, a tensegral understanding is beginning to be developed for treatments in allied health including osteopathy [43] and in oncological diagnosis [44].…”
Section: Microgravity May Promote Mental Illnessmentioning
confidence: 99%